2019
DOI: 10.1080/00480169.2019.1596524
|View full text |Cite
|
Sign up to set email alerts
|

Associations between lamb growth to weaning and dam udder and teat scores

Abstract: Aims: To investigate associations between lamb growth to weaning and dam udder and teat scores measured at pre-mating, pre-lambing, docking and weaning. Methods: Mature Romney ewes (n = 1,009) were enrolled from a commercial sheep flock located near Masterton, in the Wellington region of New Zealand in 2017. A range of udder and teat traits were scored in all ewes, using visual assessment and palpation, at pre-mating, pre-lambing, docking and weaning. During the lambing period, each newborn lamb was matched to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…However these scores do not provide an indication of future performance, therefore further investigation into the impact of the present season's score on future seasons' lamb survival is required. These results should also be considered in association with the results of our companion paper examining relationships between udder traits and lamb growth rates to weaning (Griffiths et al 2019).…”
Section: Discussionmentioning
confidence: 65%
“…However these scores do not provide an indication of future performance, therefore further investigation into the impact of the present season's score on future seasons' lamb survival is required. These results should also be considered in association with the results of our companion paper examining relationships between udder traits and lamb growth rates to weaning (Griffiths et al 2019).…”
Section: Discussionmentioning
confidence: 65%
“…It can be then suggested that the S. epidermidis overload during suckling may affect the development of rats in the long term. In this regard, a study by Griffiths et al reported lower growth rates in the offspring of dams with clinical mastitis at weaning ( 31 ) however this finding is not in agreement with the increase observed at 42 days.…”
Section: Discussionmentioning
confidence: 82%
“…Effect of treatment (Control n = 24 vs. Heavy n = 24) on the least square means (95% confidence limits) of udder palpation, the percentage (95% CL) of asymmetric udders and least square means ± SE of udder height, circumference, volume during pregnancy (P107), early lactation (L29) and weaning (L100) The difference observed in udder palpation score was seen only during pregnancy and was relatively small suggesting the udders had a score that was considered 'normal' (Griffiths et al 2019). The lack of difference in lamb growth and morphological traits between treatment groups suggests that greater liveweight gains prior to puberty had no impact on mammary gland morphological development and on the growth of their lambs.…”
Section: In Vitro Gas Production Of Hydroponic Green Forage From Corn Oat and Barley Seedmentioning
confidence: 98%
“…Udder scoring, morphology, live weights of ewe lambs, and subsequently their progeny were undertaken at 107 days of pregnancy (P107), 29 days of lactation (L29) and at weaning (L100). The scores were adapted from Griffiths et al (2019) and included udder and teat palpations, udder depth score and udder symmetry. Udder palpation scores 1, 2, 3 were diffuse soft, diffuse firm and soft consistency with nodule(s) and scores 4 and 5 being firm with nodule(s) and diffuse hard consistency.…”
Section: In Vitro Gas Production Of Hydroponic Green Forage From Corn Oat and Barley Seedmentioning
confidence: 99%